Implementation of Energy Management Concept and Energy Management System in High Rise Office Building - Marsul Siregar; Firma Purbantoro; Tajuddin Nur (Fakultas Teknik Universitas Langlangbuana, 2019)
Energy Management Concept as part of Green Building Concept is focused to Improve Energy Efficiency Index (EEI) and Water Consumption Index (WCI). The Implementation Energy Management Concept in an office buildings of this study based on the management system model of continual improvement ISO 50001:2011. The purpose of this study was to determine the extent to which the implementation of green building principles in Office Buildings. This study took the case study in an office building in Jakarta Indonesia that has two towers, each tower has 32 floors and 3 basement floors. The method used is descriptive with respect to GREENSHIP Rating Tools for existing building which consists of six categories; Appropriate Site Development (ASD), Energy Efficiency & Conservation (EEC), Water Conservation (WAC), Material Resources & Cycle (MRC), Indoor Air Health & Comfort (IHC) and Building & Environments Management (BEM). The results show that implementation the Energy Management Concept could also made energy performance more efficient, after Implementing through Retrofitting of the Chiller System, Recycle Waste Water, Replacement of Conventional lamp to Energy Saving LED and also Training and Education to all employees and tenants. From comparing data research before implementation of Energy Management Concept in 2014 and after Implementation and retrofitting in 2016, 2017 & 2018, it is found that Energy Efficiency Index (EEI) from 238.8 kwh/m2/Years to 134,04kwh/m2/Year and Water Consumption Index (WCI)From 50 liter/person/Day to 27.18 Liter/person/Day. And the saving cost from electricity bill payments is IDR. 466,803,325.67 / month (18%) and roughly will Break Event Point (BEP) for 3.86 Years